TEACHERS’ BELIEFS AND CLASSROOM PRACTICES IN TEACHING CONTENT SUBJECTS THROUGH EMI - Ulfah Oktaviani; Soni Mirizon; Machdalena Vianty (English Review: Journal of English Education, 2021)
The urge of 4.0 industrial revolutions has made the growth of English as a medium of instruction (EMI) in the educational field unbearable. The beliefs of EMI more or less would give a contribution to the teaching and learning process. This study aimed to investigate teachers’ beliefs towards EMI, to find out how the beliefs reflect in their classroom practices, and the challenges that teachers encounter in teaching content subjects through EMI. The qualitative in case study design was applied and questionnaires, observation, and interviews were used to collect the data. The observations and interviews data were analyzed through thematic analysis and the questionnaire data were analyzed by using descriptive statistical analysis. The findings of this study showed that most content subject teachers at SIS Palembang had a strong belief towards EMI. In the classroom practices, it was found that all teachers put into practiced what they believed in teaching content subjects through EMI such as they used English during the class, applied some strategies to illustrate new vocabulary, used prescribed teacher guide books, provided clear and explicit instructions, engaged the students, delivered the content greatly, and rarely did the code switching, The challenges they encountered in teaching content subjects through EMI included language barriers, class discussion engagement, and lesson preparation.